2014
DOI: 10.1002/chem.201303853
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐to‐Ligand Alkyl Migration Inducing Carbon–Sulfur Bond Cleavage in Dialkyl Yttrium Complexes Supported by Thiazole‐Containing Amidopyridinate Ligands: Synthesis, Characterization, and Catalytic Activity in the Intramolecular Hydroamination Reaction

Abstract: Neutral Y(III) dialkyl complexes supported by tridentate N(-) ,N,N monoanionic methylthiazole- or benzothiazole-amidopyridinate ligands have been prepared and completely characterized. Studies on their stability in solution revealed progressive rearrangement of the coordination sphere in the benzothiazole-containing system through an unprecedented metal-to-ligand alkyl migration and subsequent thiazole ring opening. Attempts to synthesize hydrido species from the dialkyl precursor led to the generation of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 124 publications
2
28
0
Order By: Relevance
“…Pyridine dearomatization in the presence of Group IV transition metals is unprecedented, except for reactions that involve redox‐active ligands in the presence of selected metallocenes (Figure ; I ) . However, organolanthanide complexes are well known to undergo intramolecular metal‐to‐ligand alkyl migrations that cause pyridine dearomatization (Figure ; II ), which include deeper and unpredictable ligand rearrangements . Examples of pyridine dearomatization have also been described with a variety of late‐transition‐metal complexes (Figure ; III )…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine dearomatization in the presence of Group IV transition metals is unprecedented, except for reactions that involve redox‐active ligands in the presence of selected metallocenes (Figure ; I ) . However, organolanthanide complexes are well known to undergo intramolecular metal‐to‐ligand alkyl migrations that cause pyridine dearomatization (Figure ; II ), which include deeper and unpredictable ligand rearrangements . Examples of pyridine dearomatization have also been described with a variety of late‐transition‐metal complexes (Figure ; III )…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was demonstrated that the activity of cationic alkyl rare-earth metal complexes in intramolecular hydroamination of aminoolefin is higher than that of neutral alkyl species. 25 The cationic alkyl species generated from 7 by the treatment with B(C 6 F 5 ) 3 , [HNMe 2 Ph][B(C 6 F 5 ) 4 ], [Ph 3 C][B(C 6 F 5 ) 4 ] (toluene, 20 °C) were tested as precatalysts for intermolecular hydroamination of styrene with pyrrolidine. Surprisingly in all cases no conversion was detected.…”
Section: Catalysis Of Olefin Hydroelementation Reactionsmentioning
confidence: 99%
“…Thus, the lengths of Y–C bonds between the yttrium center and terminal CH 2 SiMe 3 group in complexes 6 – 9 differ slightly (2.438(2) ( 6 ), 2.379(3) ( 7 ), 2.444(2) ( 8 ), and 2.462(2) ( 9 ) Å, respectively), and this deviation is in line with different coordination numbers of Y ions. However, all these values fall into the region characteristic for yttrium alkyl species supported by amidopyridinato, amidinato, and substituted cyclopentadienyl ligands. The bonds between yttrium ions and carbon atoms of bis­(pyrazolyl)­methyl ligands turned out to be substantially longer (2.553(2) Å, 6 ; 2.547(2) Å, 7 ; 2.564(2) Å, 8 ; 2.535(2) Å, 9 ) compared to YCH 2 SiMe 3 .…”
Section: Resultsmentioning
confidence: 93%